Impact of Cooling Media on The Tensile Strength of SMAW Welding on AISI 1060 Carbon Steel - Marthen Paloboran; Thesya Atarezcha Pangruruk; Thomas Pagasis; Rey Rahmad (Diponegoro University, 2026)
The cooling process of steel after undergoing the welding process will affect the changes in the microstructure of the steel and will also have an impact on the tensile strength, elasticity and strain and brittleness of the steel. This study aims to determine the mechanical properties of AISI 1060 steel, including tensile strength, elasticity, and length increase after the material goes through the welding process. The welding method applied in this study is V-weld with a position of 1G, which is carried out on 9 specimens with dimensions of 200 x 20 x 8 mm (L x W x T). The welded specimens are then cooled for 10 minutes before tensile testing is carried out. The results of the study showed that the used oil cooling medium has a greater tensile strength compared to the cooling media of tap water and well water. The high tensile strength value causes the steel to undergo a greater strain process, resulting in strain values of 2.2380%, 0.053%, and 0.1063% for steel cooled with used oil, tap water, and well water, respectively.